ChemInform Abstract: A Sequential One‐Pot Protocol for the Synthesis of Dihydrobenzo[6, 7]indolo[3′, 4′:3, 4, 5]azepino[2, 1‐a]isoquinolines Using a Gold—Silver Combined Catalyst. Issue 40 (12th September 2013) - Saifuddin, Mohammad; Samala, Srinivas; Krishna, Deevi G. Venkata; Kundu, Bijoy
Abstract Indole‐based substrates react with a broad spectrum of aromatic aldehydes bearing a 2‐alkynyl chain to produce the title skeletons via imine formation, cationic π‐cyclization, and intramolecular hydroamination.